Objective assessment of the parameters and stability of accommodation after optical and opto-pharmacological therapy of progressive myopia in children - E. P. Tarutta; S. E. Kondratova (Российский офтальмологический журнал, 2025)
Purpose of the work: comparative evaluation of the effect of isolated optical (OT) and combined optical-pharmacological (OPT) therapy in patients with myopia on various accommodation parameters and its stability. Material and methods. Objective parameters and stability of accommodation after OT and OFT were determined in 31 patients aged 8–13 years with acquired myopia from –0.87 to –5.75 (on average –2.96 ± 1.60) D. Patients in the OFT group used HAL (Stellest™) spectacle lenses in combination with instillations of Mydrimax solution (Phenylephrine 5.0 % + Tropicamide 0.8 %). Patients in the OT group received isolated optical therapy. Dynamic computer accommodation was performed using a WAM-5500 (Grand Seiko, Japan) with recording of the dynamic monocular accommodation response (dyn MAR) for 10 sec with a recording frequency of at least 6 Hz. The frequency of microfluctuations (FMF) of the accommodative response (AR), the maximum AR range, and the character of the signal isoline trend during the recording period were also estimated. The AR value and the coefficient of microfluctuations (CMF) were recorded using an Acomoref 2 K-2 automatic ref-keratometer (Righton). Additionally, differences in subgroups with different levels of dyn MAR stability were estimated: downward, upward, and constant MAR trend. Results. Continuous wearing of glasses with HAL lenses with full myopia correction leads to a reliable increase in the static and maximum dyn MAR. The lowest values of the average dynamic MAR are associated with a downward trend, which confirms the specificity of the “AO trend” criterion in diagnosing accommodation instability. Due to OFT, an increase in accommodation stability was noted — the AO trend acquired a constant character. In the OT group, such favorable changes were not noted. An increase in the AO value due OT and OFT was accompanied by an increase in the FMF and AO range. Conclusion. The combination of OT with regular instillations of the Midrimax increases the effectiveness of treatment of accommodation disorders in children with progressive myopia.